Effects of Priming and Audience Design on the Explicitness of Referring Expressions: Evidence From a Confederate Priming Paradigm. Issue 9 (20th October 2020) - Loy, Jia E.; Bloomfield, Stephanie J.; Smith, Kenny
ABSTRACT: In formulating a referring expression, speakers may choose between an explicit expression (such as a proper name or a noun phrase) or a reduced form such as a pronoun. We investigated whether speakers are influenced by their conversation partners to produce full noun phrases instead of pronouns and whether this differs depending on whether their partner was a native or a nonnative English speaker. Participants took turns describing and matching cartoons with a (confederate) partner, who used either full noun phrases or pronouns when referring to discourse entities. We found that participants were more explicit or less explicit in their own referring expressions depending on their partner's behavior on the turn before and adapted to the same extent with native and nonnative partners. We conclude that speakers adapt their production of referring expressions based on what their partners say but do not make strategic adjustments based on who their partner is.